Laboratory Simulation for Reducing Water Turbidity by Water Hyacinth to Meet Coal Wastewater Discharge in Paringin Pit Lake - Suhernomo, Suhernomo; Fatah, Luthfi; Saidy, Rizalli Akhmad; Pratmadi, Bambang Joko (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Coal mining with an open-pit mining method can created the formation of pit lake filled with high turbidity water which has the potential to pollute and cannot be utilized if not managed properly. Treatment to reduce water turbidity to meet quality standards with chemicals is a common, but during post mining period, it is necessary to reduce the processing, which is expensive and uncertain, turning into a natural process and lower cost. The aim of this study is to analysis on the role of water hyacinth as macrophytes in reducing water turbidity on three different water sources for treatment. Water hyacinth is an aquatic plant that can be used to reduce water pollution such as high levels of turbidity in water quality. The experimental results showed that not significant on TSS < 200 mgL-1 but significantly different results, on TSS values between 200 - 400 mgL-1 and TSS > 400 mgL-1 and to be the basic reference data of the number of plants used in experiment to enlarge it on a field scale.